Utilization of nitrogen-fixing endophytic bacteria to improve Cassava yield and nutrient uptake - DO Quang Trung; Manh Ha NGUYEN (Acta Agriculturae Slovenica)
This study investigated the potential of endophytic bacteria isolated from native cassava (Manihot esculenta KM98-7) to enhance plant growth and yield under greenhouse and field conditions. Eleven bacterial strains (TL1 to TL11) were isolated and assessed for nitrogen fixation, phosphate solubilization, and indole acetic acid (IAA) synthesis. TL4 and TL8 exhibited superior capabilities, with TL8 producing the highest levels of NH4+ (14.95 mg l-1) and IAA (46.57 mg l-1). Molecular identification revealed that TL4 and TL8 were closely related to Burkholderia cenocepacia and Bacillus aryabhattai. Greenhouse trials showed that inoculation with TL8 significantly increased plant height, leaf number, and tuber yield, comparable to 90 kg urea ha-1 application. Field experiments confirmed these findings, with the 60 kg urea ha-1 + TL8 treatment achieving similar yields to 90 kg urea ha-1 without bacterial inoculation. This study demonstrates that integrating nitrogen-fixing bacterial inoculants, particularly strain TL8, with reduced nitrogen fertilization can maintain high cassava productivity while promoting sustainable agricultural practices.